Publications: Climate change - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
IFPRI’s mission is to provide research-based policy solutions to sustainably reduce poverty and end hunger and malnutrition. Recent publications share knowledge and data that can contribute to addressing the challenges of climate change.